CuCo-N / CB catalyst, preparation method thereof and application of the catalyst in catalyzing 5-hydroxymethylfurfural to prepare 2,5-furan dicarboxylic acid
Patent Information
- Application Number
- CN202611185133.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]为了克服现有技术中CuCo-N-C系列催化剂载体制备工艺复杂、比表面积小以及催化剂制备工艺复杂、不够经济环保等缺点,本发明提供了一种炭黑(CB)负载钴氮键和铜的双金属催化剂(CuCo-N/CB)及其催化氧化5-羟甲基糠醛制备2,5-呋喃二甲酸的方法
(1)催化剂采用廉价易得的炭黑载体和非贵金属钴、铜盐作为原料,无需贵金属和石墨烯、碳纳米管等昂贵碳材料,显著降低了催化剂制备成本,具有良好的经济性;
Smart Images

Figure CN122999253A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst preparation and biomass catalytic conversion technology, and relates to a CuCo-N / CB catalyst and its preparation method, as well as the application of the catalyst in the catalytic preparation of 2,5-furandicarboxylic acid from 5-hydroxymethylfurfural. Specifically, it relates to a CuCo-N / CB (carbon black) catalyst, the preparation method of the catalyst, and the application of the catalyst in the catalytic preparation of 2,5-furandicarboxylic acid from 5-hydroxymethylfurfural. Background Technology
[0002] 5-Hydroxymethylfurfural (HMF), an important platform compound obtained from the hydrolysis and dehydration of lignocellulosic biomass, can be further converted into high-value-added chemicals such as 2,5-furandicarboxylic acid (FDCA) through selective oxidation. FDCA is a key monomer for the synthesis of bio-based polyesters (such as polyethylene furanate) and holds promise as a substitute for traditional petroleum-based terephthalic acid, showing broad application prospects in the fields of biodegradable plastics and green materials. Therefore, developing efficient catalysts to achieve the selective oxidation of HMF to prepare FDCA is of great significance.
[0003] In recent years, catalysts for the thermocatalytic oxidation of HMF to FDCA have mainly fallen into two categories: noble metal catalysts and non-noble metal catalysts. Noble metal catalysts (such as Au, Pt, and Pd) exhibit excellent catalytic activity and FDCA selectivity under mild conditions, but their large-scale industrial application is limited due to the scarcity and high cost of precious metal resources. Therefore, low-cost and abundant transition metal catalysts have gradually become a research hotspot, with Co and Cu non-noble metal catalysts being the most extensively studied. (TKT Le, S. Kongparakul, H. Zhang, J. Zhao, G. Guan, N. Chanlek, TTV Tran and C. Samart, Highly efficient liquid-phase oxidation of 5-hydroxymethylfurfural over Co-Cu / activated carbon catalysts.) Molecular Catalysis, 2023, 539. A Co-Cu bimetallic supported activated carbon catalyst (Co-Cu / AC) was used for the selective oxidation of HMF to FDCA in an aqueous system with H2O2 as the oxidant and Na2CO3 as the base additive. The optimal catalyst was 4Co-Cu / AC (Co:Cu mass ratio 4:1, total metal loading 20 wt%), achieving a HMF conversion of 99% and an FDCA yield of 92% under the conditions of 170 ℃, 9 h of reaction, and 10 wt% catalyst. The relatively low metal activity of the catalyst resulted in a high required temperature (170 ℃) and a long reaction time (9 h). Wei Jiang, Dongjun Wang, Xunliang Deng, Yuxin Gao, WeizongWang, Tengjie Ge, Chengkang Zhao, Yong Sun, Oxygen vacancy boosted oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid over CuCoOx. Molecular Catalysis ,2024,113917,2468-8231 used a bimetallic oxide catalyst CuCoO x (Cu:Co molar ratio 1:1, prepared by coprecipitation method) was used to selectively oxidize HMF in an aqueous system with sodium hypochlorite (NaClO) as the oxidant to prepare FDCA without the need for external alkali. Under optimal conditions (room temperature, 15 min, NaClO / HMF molar ratio 5:1), the HMF conversion rate reached 100%, and the FDCA yield reached 96.4%. This system achieved rapid oxidation of HMF to FDCA, but the oxidant is NaClO, which is not in line with the concept of green chemistry and is uneconomical compared with experiments using O2 as the oxidant. Some researchers have found that combining Co and N to form Co-N bonds increases the activity of the catalyst, so they introduce N components into the catalyst components or support. TKT Le, HTD Nguyen, S. Kongparakul, H. Zhang, G. Guan, N.Chanlek, TNM An, TTV Tran, C. Samart, ChemistrySelectOn August 2023, 2023, at 202302926, a melamine sponge-derived carbon-supported Co-Cu bimetallic catalyst (4Co-Cu / MS, Co:Cu mass ratio 4:1, total metal loading 20 wt%) was used for the selective oxidation of HMF to FDCA in an aqueous system with H2O2 as the oxidant and Na2CO3 as the alkali additive. Under optimal conditions (170 ℃, atmospheric pressure, reaction time 7 h, catalyst loading 10 wt%), the HMF conversion reached 100% and the FDCA yield reached 93%. The catalyst embeds Co and Cu into the carbon framework of the melamine sponge via adsorption-carbonization. However, the oxidant H2O2 is insufficient compared to O2, and the reaction temperature is relatively high (170 ℃), indicating room for optimization compared to a milder catalytic system. Meiyun Zhang, Penghua Che, Hong Ma, Xin Liu, Shujing Zhang, Yang Luo, Jie Xu, Dual-metal synergy unlocking ROS-free catalysis for rapid aerobic oxidation of 5-hydroxymethylfurfural at room temperature. Chinese Journal of Catalysis In 2024, pp. 144-156, a CuCo / NC bimetallic nanocatalyst (Cu:Co molar ratio approximately 4:6, supported on a nitrogen-doped carbon support) was used for the selective oxidation of HMF in an aqueous system with O2 as the oxidant and NaOH as the alkali additive to prepare FDCA. Under optimal conditions (25 °C, 1 MPa O2, 6 h reaction time, NaOH / HMF molar ratio 4:1), the HMF conversion rate was >99.8%, and the FDCA selectivity reached 94.5%. However, the catalyst support was constructed using melamine as a raw material, which produces yellow fumes during calcination, polluting the environment. Furthermore, the sintered melamine product has a small specific surface area, making it unsuitable as a support. (Jing, T., Yang, S., Feng, Y.) et al. Selective and effective oxidation of 5-hydroxymethylfurfural by tuning the intermediates adsorption on Co-Cu-CN x . Nano Res. 16, 6670–6678 (2023). A nitrogen-doped carbon-supported Co-Cu bimetallic nanoparticle catalyst (Co-Cu) was developed using zeolite imidazolium ester framework-8 (ZIF-8) derived nitrogen doped carbon. 1.4 -CN xA catalyst (Cu / Co molar ratio 1.4:1) was used in an aqueous system for the selective oxidation of HMF (hydrofuran) with O2 as the oxidant and Na2CO3 as the base additive to prepare FDCA. Under optimal conditions (100 °C, 1 MPa O2, 12 h reaction time, Na2CO3 / HMF molar ratio 2:1), the HMF conversion reached 100%, and the FDCA yield reached 96%. The catalyst preparation process is complex and requires a long time. (T. Jing, S. Yang, T. Li, Y. Wan, H. Jia, Y. Feng, Y. Zuo, D. Rao, Atomic Co / Cu Dual-Metal for Rapid Conversion of 5-Hydroxymethylfurfural under Ambient Pressure). Adv. Funct. Mater. 2024, 34, 2407335. An a-Co / Cu-NC catalyst (Co loading 0.6 wt%, Cu loading 0.22 wt%, ZIF-8 derived nitrogen-doped carbon as support) was used for the selective oxidation of HMF to FDCA in an aqueous system with O2 as the oxidant and Na2CO3 as the alkali additive. Under optimal conditions (90 ℃, atmospheric pressure O2 flow, reaction time 8 h), the HMF conversion was >99%, and the FDCA yield reached 98%. Compared with the previous paper, this reaction showed some optimization in reaction time, temperature, and oxygen pressure, but the catalyst preparation process remains relatively complex. H. Liu, N. Ding, J. Wei, X. Tang, X. Zeng, Y. Sun, T. Lei, H. Fang, T. Li, L. Lin, ChemSusChem 2020, 13 4151. A ZIF-8-derived nitrogen-doped carbon-supported CoCu bimetallic nanoparticle catalyst (Co7Cu3-NC, Co / Cu molar ratio 7:3, total metal loading ~2 wt%) was used for the oxidative esterification of HMF in a methanol system with O2 as the oxidant under alkaline conditions to prepare dimethyl furanate (FDMC). Under optimal conditions (80 ℃, 2 bar O2, 4 h), the HMF conversion reached 100%, and the FDMC yield reached 95%. This catalyst can be recycled at least four times after regeneration with H2 at 400 ℃, but direct reuse suffers from severe deactivation (the FDMC yield drops from 95% to 34% in the second cycle), requiring high-temperature regeneration to restore activity.
[0004] Carbon black (CB), as an industrial-grade carbon material, possesses unique potential advantages as a carrier in the catalytic system for the liquid-phase oxidation of HMF to FDCA. Firstly, carbon black exhibits a high degree of graphitization and excellent electrical and thermal conductivity; its highly ordered sp...2 The hybrid carbon layer structure facilitates rapid electron transfer in catalytic reactions, which is particularly important for oxidation reactions involving molecular oxygen activation and the generation and transport of reactive oxygen species (ROS). It effectively promotes the electronic synergistic effect between the active metal component and the support, accelerating the redox cycle. Secondly, the carbon black surface contains appropriate amounts of oxygen-containing functional groups such as hydroxyl, carboxyl, carbonyl, and lactone groups. These groups can serve as anchoring sites for metal ions, achieving efficient loading and uniform dispersion of metal nanoparticles. Simultaneously, the type and density of these functional groups can be flexibly controlled through heat treatment, acid treatment, or oxidation modification, thereby achieving targeted optimization of the metal-support interaction and improving the catalyst's activity and stability. Thirdly, carbon black possesses a controllable specific surface area and pore structure. By selecting different varieties (such as acetylene black, furnace black, and Ketjen black), a balance can be achieved between conductivity, specific surface area, and mesoporous ratio—an appropriate proportion of mesoporous structure facilitates the diffusion and mass transfer of reactant HMF and product FDCA, reducing catalyst deactivation due to product pore blockage. Fourth, compared with novel carbon materials such as carbon nanotubes and graphene, carbon black has a mature industrial preparation process, a wide range of raw material sources, good batch stability, and a significant price advantage. It also has good molding and processing performance, making it easy to form tablets, extrudes, and other molding operations. It is suitable for continuous industrial reaction devices such as fixed beds and trickle beds, meeting the engineering requirements of catalyst supports for large-scale FDCA production.
[0005] To date, there have been no reports on the use of carbon black (CB) as a support for CoCu-based catalysts, followed by nitrogen doping via 1,10-o-phenanthroline-assisted pyrolysis, for the selective oxidation of HMF to FDCA. This invention addresses this gap by proposing a CuCo-N / CB catalyst system using readily available and inexpensive carbon black as the support, CoCu as the active component, and introducing nitrogen from 1,10-o-phenanthroline pyrolysis. This catalyst design is expected to possess excellent catalytic activity, efficient electron transport and mass transfer capabilities, and a simple and easily scaled-up preparation process, meeting the demands of industrial applications. It provides an economical and efficient technical route for the high-value conversion of biomass platform compound HMF, demonstrating significant research value and broad application prospects. Summary of the Invention
[0006] To overcome the shortcomings of existing CuCo-NC series catalyst supports, such as complex preparation processes, small specific surface areas, and complex catalyst preparation processes that are not economical or environmentally friendly, this invention provides a bimetallic catalyst (CuCo-N / CB) supported on carbon black (CB) with cobalt nitrogen bonds and copper, and a method for catalytic oxidation of 5-hydroxymethylfurfural to prepare 2,5-furandicarboxylic acid.
[0007] The inventive concept of this invention is as follows: using inexpensive, widely available carbon black (CB) with a high graphitization content as a carrier, and cobalt acetate as the cobalt source, a 1,10-phenanthroline ligand-assisted pyrolysis method is employed to introduce nitrogen components, thereby preparing a CuCo-N / CB catalyst. After calcination, highly dispersed Co is formed. 0 / Co 2+ and Cu 0 / Cu 2+ The active sites, after hydrogen pre-reduction treatment, can be directly used for the catalytic oxidation of HMF to FDCA. Under aqueous solvent, 3 MPa oxygen pressure, and 80 °C conditions for 7 h, complete HMF conversion can be achieved, with FDCA selectivity exceeding 95%. Carbon black not only effectively disperses the CoCu active components but also promotes the interaction between CoCu species and the N component with the support, thereby improving catalyst activity and stability. The prepared catalyst is simple in process, low in cost, and requires no complex support construction or pretreatment, providing a novel catalyst system suitable for industrial application for the efficient conversion of HMF to FDCA.
[0008] A CuCo-N / CB catalyst is provided, wherein the catalyst uses carbon black CB as a support and provides oxidation catalysis function with Co-N and Cu, wherein the molar ratio of Co to Cu is 6:1 to 1:2, preferably 4:1.
[0009] A method for preparing a CuCo-N / CB catalyst, using a supported-pyrolysis method, is described below: (1) Preparation of metal solution: Weigh a certain amount of cobalt acetate tetrahydrate Co(CH3COO)2·4H2O and copper nitrate trihydrate Cu(NO3)2·3H2O, and dissolve them in deionized water to prepare a solution; (2) Introduction of N component: Weigh a certain amount of 1,10-o-phenanthroline, add it to the above solution, heat it in a water bath to 40-60℃ and stir it evenly.
[0010] (3) Loading: After adding acetylene carbon black carrier to the solution prepared in step (2), stir at room temperature for 1-3 h, and then perform vacuum rotary evaporation at 50-70 ℃ to evaporate all the water so that all the metal salt is loaded on CB. (4) Drying: Place the sample from step (3) in a vacuum drying oven at 50-70 ℃ and dry for 8-20 h; (5) Calcination: The dried sample is placed in a tube furnace and heated to 600-900 ℃ at 2-10 ℃ / min under a nitrogen atmosphere. After holding at this temperature for 1-3 h, it is naturally cooled to room temperature. Then, it is subjected to reduction pretreatment at 300-500 ℃ at 5-15 ℃ / min under a 3-10 vol% H2 / Ar atmosphere. After holding at this temperature for 1-3 h, it is naturally cooled to room temperature to obtain the CuCo-N / CB catalyst.
[0011] Furthermore, in step (1), the amount of Co carried per gram of CB is 1.0–5.0 mmol·g. -1 CB, preferably 1.5-3.0 mmol·g -1 CB; the amount of Cu supported per gram of CB is 0.1–2.0 mmol·g. -1 CB, preferably 0.5-1.0 mmol·g -1 CB; Furthermore, in step (2), the amount of 1,10-phenanthroline supported per gram of CB is 1.0–8.0 mmol·g. -1 CB, preferably 3.0-4.0 mmol·g -1 CB.
[0012] Furthermore, in step (5), the calcination temperature is preferably 800 ℃ and the reduction temperature is preferably 400 ℃.
[0013] The application of a CuCo-N / CB catalyst in the preparation of 2,5-furandicarboxylic acid from 5-hydroxymethylfurfural is achieved through the following steps: 5-Hydroxymethylfurfural (HMF), CuCo-N / CB catalyst, and potassium hydroxide were added to a reaction vessel. Water was used as the reaction solvent, and oxygen was introduced into the reaction vessel as an oxidant. An intermittent oxidation reaction was carried out under magnetic stirring to produce 2,5-furandicarboxylic acid.
[0014] Furthermore, the HMF oxidation reaction temperature is 60–100 °C, the oxygen pressure is 1–4 MPa, and the reaction time is 1–9 h. More preferred reaction conditions are: reaction temperature 80 °C, oxygen pressure 3 MPa, and reaction time 7 h.
[0015] The present invention has the following advantages and effects compared with the prior art: (1) The catalyst uses inexpensive and readily available carbon black support and non-precious metal cobalt and copper salts as raw materials, without the need for precious metals and expensive carbon materials such as graphene and carbon nanotubes, which significantly reduces the catalyst preparation cost and has good economic efficiency. (2) The catalyst was prepared by 1,10-phenanthroline ligand-assisted pyrolysis, utilizing the reaction of phenanthroline and Co 2+ / Cu 2+ The strong coordination effect of the ligand achieves uniform anchoring and spatial isolation of metal ions at the molecular level, effectively inhibiting the aggregation of metal particles during pyrolysis and promoting the formation of atomically dispersed Co / Cu bimetallic sites. At the same time, the ligand itself acts as a nitrogen and carbon source, enabling in-situ nitrogen doping of the carbon black carrier during pyrolysis without the need for additional nitrogen sources or template agents; thus avoiding the pollution problem caused by the thermal decomposition of CN raw materials such as melamine. (3) The preparation process adopts pyrolysis-hydrogen reduction process, which avoids complex steps such as hydrothermal reaction, template agent construction or traditional high temperature carbonization. The process conditions are mild and controllable, with good repeatability, and have the feasibility of industrial scale-up. (4) The CoCu bimetallic active components in the prepared CoCu-N-CB catalyst are highly dispersed on the surface of CB with a large specific surface area. Combined with the excellent electrical and thermal conductivity of the CB support and the electronic modulation effect induced by N doping, the synergistic effect between Co and Cu and the metal-N coordination structure effectively regulate the d-band center and electron cloud density of the catalyst, enhance the hydrogen activation or molecular oxygen activation ability, and significantly improve the reaction activity and selectivity of HMF oxidation to FDCA. (5) Under relatively mild reaction conditions not exceeding 100℃, the HMF conversion rate can reach 100%, and the selectivity of the target product FDCA can reach more than 95%, demonstrating excellent catalytic performance and product selectivity. (6) The steric hindrance effect of 1,10-phenanthroline ligand and the strong anchoring effect of N doping sites, as well as the tight binding with CB, endow the catalyst with excellent structural stability and anti-sintering ability. The metal active components are not easy to agglomerate or be lost during the reaction process, and the catalyst has excellent recycling performance and long-term stability.
[0016] In summary, the CuCo-N / CB catalyst provided by this invention has the advantages of inexpensive and readily available raw materials, simple and controllable preparation process, excellent catalytic performance, and good stability, and has broad application prospects in the field of high-value conversion of biomass platform compounds HMF. Attached Figure Description
[0017] Figure 1 This is a technical roadmap for the preparation of FDCA from HMF catalyzed by CuCo-N / CB. Detailed Implementation
[0018] The present invention will be further described in detail below with reference to embodiments, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the experimental methods used in the present invention are all conventional methods, and the experimental equipment, materials, reagents, etc. used can be purchased from chemical companies.
[0019] Examples 1-4: Batch Reactions at Different Reaction Temperatures 1. Catalyst preparation: Cu1Co4-N / CB catalyst was prepared by 1,10-phenanthroline ligand-assisted pyrolysis. The specific steps are as follows: (1) Preparation of metal solution: Weigh 582.06 mg of cobalt acetate tetrahydrate Co(CH3COO)2·4H2O and 120.8 mg of copper nitrate trihydrate Cu(NO3)2·3H2O, and prepare a 0.0167 mol / L solution with 150 mL of deionized water; (2) Introduction of N component: Weigh 720.84 mg of 1,10-o-phenanthroline, add it to the above solution, heat it in a water bath to 50°C and stir; (3) Loading: After adding 1g of carbon black carrier to the solution prepared in step (2), stir for 1 h in a water bath at 50°C, and then evaporate under vacuum at 60°C to remove all the water. (4) Drying: Place the sample (3) in a vacuum drying oven at 60 ℃ and dry for 12 h, then grind it into powder using an agate mortar and pestle; (5) Calcination: The dried sample was placed in a tube furnace and heated to 800℃ at 5℃ / min under a nitrogen atmosphere. After holding at this temperature for 2 h, it was naturally cooled to room temperature. Then, it was subjected to reduction pretreatment at 10℃ / min to 400℃ under a 5 vol% H2 / Ar atmosphere. After holding at this temperature for 2 h, the temperature was lowered to room temperature to obtain Cu1Co4-N / CB catalyst. The sample was then taken out and sealed for storage.
[0020] 2. Reaction Test: The performance of the Cu1Co4-N / CB catalyst in catalyzing the oxidation of 5-hydroxymethylfurfural was tested using a batch reaction method. The specific steps were as follows: (1) Take a mechanically stirred high-pressure reactor, add 0.25 mmol 5-hydroxymethylfurfural, 10 mL water, 50 mg Cu1Co4-N / CB catalyst and 100 mg potassium hydroxide to it, tighten the reactor and check the airtightness of the device. After ensuring that the device does not leak, introduce 3 MPa O2, stir at 400 rpm, and set the specified temperature to carry out the reaction.
[0021] (2) After the reaction is complete, the liquid product is collected and analyzed by liquid chromatography. The catalyst is recovered by centrifugation.
[0022] Wherein: the conversion rate of 5-hydroxymethylfurfural = (the amount of 5-hydroxymethylfurfural at the beginning of the reaction - the amount of 5-hydroxymethylfurfural at the end of the reaction) / the amount of 5-hydroxymethylfurfural at the beginning of the reaction × 100%.
[0023] Yield of 2,5-furandicarboxylic acid = Amount of 2,5-furandicarboxylic acid at the end of the reaction / Amount of 5-hydroxymethylfurfural at the beginning of the reaction × 100%.
[0024] Selectivity for 2,5-furandicarboxylic acid = (yield of 2,5-furandicarboxylic acid / conversion of 5-hydroxymethylfurfural) × 100%.
[0025] The liquid chromatography analysis conditions were as follows: C18 column, mobile phase (10% methanol and 90% sodium formate solution), temperature 40℃, flow rate 0.6 mL / min, UV detector UV = 220 nm, external standard method.
[0026] 3. The reaction results are shown in Table 1. Table 1 Results at different reaction temperatures As shown in Examples 1-4, HMF can be completely converted at a reaction temperature of 60 °C, but the selectivity for FDCA is low, with 6.4% of the intermediate product 5-hydroxymethyl-2-furanoic acid (HMFCA). As the temperature gradually increases, the selectivity for FDCA gradually increases, while the selectivity for HMFCA gradually decreases, indicating that HMFCA is gradually oxidized to FDCA, and the oxidation reaction is progressing progressively. When the reaction temperature reaches 80 °C, HMF achieves 100% conversion and 95.2% FDCA selectivity. Even at temperatures above 90 °C, shortening the reaction time can still result in high-selectivity FDCA formation.
[0027] Examples 3 and 5-9: Batch reactions with different reaction times 1. Catalyst preparation: Same as the catalyst preparation process in Examples 1-4.
[0028] 2. Reaction test: The operation process is the same as the reaction test process in Examples 1-4. The specific reaction conditions are as follows: after ensuring that the device is airtight, introduce O2 at a specified pressure of 3MPa, stir at 400rpm, and set the temperature to 80℃ for 1-8 hours.
[0029] 3. The reaction results are shown in Table 2.
[0030] Table 2 Results of the reaction at different times As shown in Examples 3 and 5-9, under the condition of 80 °C, when the reaction time is 1 h, HMF can be 100% converted, and the selectivity of FDCA is 70.9%. As the reaction time increases, the selectivity of FDCA also increases, reaching 95.2% after 7 h. However, after 8 h, the selectivity of FDCA decreases slightly. This indicates that if the reaction time is too long, the catalyst will continuously generate highly active ROS such as ·OH (hydroxyl radical), which will also lead to peroxidation or polymerization after FDCA formation, thereby reducing the net selectivity of FDCA.
[0031] Examples 3 and 10-12: Batch reactions at different reaction pressures 1. Catalyst preparation: Same as the catalyst preparation process in Examples 1-4.
[0032] 2. Reaction test: The operation process is the same as the reaction test process in Examples 1-4. The specific reaction conditions are as follows: after ensuring that the device is airtight, introduce O2 at the specified pressure, stir at 400 rpm, and set the temperature to 80℃ for 7 hours.
[0033] 3. The reaction results are shown in Table 3.
[0034] Table 3 Results of reactions under different oxygen pressures Examples 3 and 10-11 show that under conditions of 1 MPa-3 MPa and 80°C for 7 hours, the HMF conversion rate can reach 100%. Even at an O2 pressure of 1.0 MPa, good catalytic activity is observed, with an FDCA yield of 87.8%, although some intermediate product HMFCA remains unconverted. When the O2 pressure is increased to 2.0 MPa, all HMF is converted, and the FDCA yield reaches 91.2%. When the O2 pressure is increased to 3.0 MPa, the FDCA yield reaches 95.2%. This indicates that O2 at 3.0 MPa in the reaction system can generate a large amount of activated oxygen through the Cu1Co4-N / CB catalyst, thereby promoting the forward reaction of HMF to FDCA. Furthermore, at O2 pressures above 3.0 MPa, the FDCA yield shows a decreasing trend. This result indicates that higher O2 pressure leads to rapid FDCA conversion catalyzed by the Cu1Co4-N / CB catalyst, followed by further FDCA reaction, resulting in reduced FDCA selectivity. Therefore, when the O2 pressure is higher, the reaction time can be shortened to ensure high FDCA selectivity.
[0035] Comparative Example 1: Batch reaction of Cu2Co3-N / CB catalyst 1. Catalyst preparation: Cu2Co3-N / CB catalyst was prepared by 1,10-phenanthroline ligand-assisted pyrolysis. The specific steps are as follows: (1) Preparation of salt solution: Weigh 436.5 mg of cobalt acetate tetrahydrate Co(CH3COO)2·4H2O and 241.6 mg of copper nitrate trihydrate Cu(NO3)2·3H2O, and dissolve them in 150 mL of deionized water to prepare a 0.0167 mol / L solution; (2) Introduction of N component: Weigh 540.63 mg of 1,10-o-phenanthroline, add it to the above solution, heat it in a water bath to 50°C and stir.
[0036] The remaining preparation steps are the same as in Examples 3-5.
[0037] 2. Reaction test: The performance of Cu2Co3-N / CB catalyst in catalyzing the oxidation of 5-hydroxymethylfurfural was tested using a batch reaction method. The specific steps were the same as in Examples 1-4.
[0038] The reaction results showed that under the action of this catalyst, the HMF conversion rate was 100% and the FDCA selectivity was 90.1%. The product contained byproducts of HMF oxidation. Under comparable conditions, the Cu1Co4-N / CB catalyst of this invention could achieve complete HMF conversion and an FDCA yield of 95.2%. Therefore, a Cu:Co molar ratio of 1:4 is superior to 2:3.
[0039] Comparative Example 2: Batch reaction of Co4-N / CB catalyst 1. Catalyst preparation: Co4-N-CB catalyst was prepared by 1,10-phenanthroline ligand-assisted pyrolysis. The specific steps are as follows: (1) Preparation of salt solution: Weigh 582.06 mg of cobalt acetate tetrahydrate Co(CH3COO)2·4H2O, and dissolve it in 150 mL of deionized water to prepare a 0.0133 mol / L solution; (2) Introduction of N component: Weigh 720.84 mg of 1,10-phenanthroline, add it to the above solution, heat it in a water bath to 50°C and stir.
[0040] The remaining preparation steps are the same as in Examples 3-5.
[0041] 2. Reaction test: The performance of the Co4-N / CB catalyst in catalyzing the oxidation of 5-hydroxymethylfurfural was tested using a batch reaction, and the specific steps were the same as in Examples 1-4.
[0042] The reaction results showed that under the action of this catalyst, the HMF conversion rate was 100% and the FDCA selectivity was 88.2%. No HMF oxidation byproducts were found in the product. Under comparable conditions, the Cu1Co4-N / CB catalyst of this invention could achieve complete HMF conversion and an FDCA yield of 95.2%. This demonstrates that the introduction of Cu improves catalytic performance.
[0043] Comparative Example 3: Batch reaction of Cu1 / CB catalyst 1. Catalyst preparation: Cu1-CB catalyst was prepared by pyrolysis. The specific steps are as follows: Preparation of salt solution: Weigh 120.8 mg of copper nitrate trihydrate Cu(NO3)2·3H2O, dissolve it in 150 mL of deionized water to prepare a 0.00333 mol / mL solution; The remaining preparation steps are the same as in Examples 3-5.
[0044] 2. Reaction test: The performance of Cu1 / CB catalyst in catalyzing the oxidation of 5-hydroxymethylfurfural was tested using a batch reaction method. The specific steps were the same as in Examples 1-4.
[0045] The reaction results showed that under this catalyst, the HMF conversion rate was 98.4%, but the FDCA selectivity was only 5%. Other byproducts of HMF oxidation were still present in the product. In contrast, under comparable conditions, the Cu1Co4-N / CB catalyst of this invention could achieve complete HMF conversion, with an FDCA yield of 95.2%.
[0046] Comparative Example 4: Batch reaction of Cu1Co4 / CB catalyst 1. Catalyst preparation: Cu1Co4 / CB catalyst was prepared by pyrolysis. The specific steps are as follows: Preparation of salt solution: Weigh 582.06 mg of cobalt acetate tetrahydrate Co(CH3COO)2·4H2O and 120.8 mg of copper nitrate trihydrate Cu(NO3)2·3H2O, and dissolve them in 150 mL of deionized water to prepare a 0.0167 mol / L solution. The remaining preparation steps are the same as in Examples 3-5.
[0047] 2. Reaction test: The performance of Cu1Co4 / CB catalyst in catalyzing the oxidation of 5-hydroxymethylfurfural was tested using a batch reaction, and the specific steps were the same as in Examples 1-4.
[0048] The reaction results showed that under this catalyst, the HMF conversion rate was 97%, but the FDCA selectivity was only 5.6%. Other byproducts of HMF oxidation were still present in the product. In contrast, under comparable conditions, the Cu1Co4-N / CB catalyst of this invention could achieve complete HMF conversion, with an FDCA yield of 95.2%. As can be seen from Comparative Examples 1-4, the catalysts Cu1 / CB and Cu1Co4 / CB, due to the lack of Co-N bonds, exhibit significantly lower catalytic activity than the invented Cu1Co4-N / CB catalyst. Furthermore, the catalysts Cu2Co3-N / CB and Co4-N / CB, due to their metal ratio and single-metal composition, also show lower catalytic activity than the Cu1Co4-N / CB catalyst. Therefore, the catalyst composition constructed by the present invention can effectively catalyze the reaction of HMF to FDCA.
[0049] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A CuCo-N / CB catalyst, characterized in that, The catalyst uses carbon black CB as a support, and the oxidation catalytic function is provided by Co-N and Cu, with a molar ratio of Co to Cu of 6:1 to 1:
2.
2. The CuCo-N / CB catalyst according to claim 1, characterized in that, The molar ratio of Co to Cu is 4:
1.
3. A method for preparing a CuCo-N / CB catalyst, characterized in that, The preparation method is a loaded-pyrolysis method, and the specific steps are as follows: (1) Preparation of metal solution: Weigh a certain amount of cobalt acetate tetrahydrate Co(CH3COO)2·4H2O and copper nitrate trihydrate Cu(NO3)2·3H2O, and dissolve them in deionized water to prepare a solution; (2) Introduction of N component: Weigh a certain amount of 1,10-o-phenanthroline, add it to the above solution, heat it in a water bath to 40-60℃ and stir it evenly; (3) Loading: After adding acetylene carbon black carrier to the solution prepared in step (2), stir at room temperature for 1-3 h, and then perform vacuum rotary evaporation at 50-70 ℃ to evaporate all the water so that all the metal salt is loaded on CB. (4) Drying: Place the sample from step (3) in a vacuum drying oven at 50-70 ℃ and dry for 8-20 h; (5) Calcination: The dried sample is placed in a tube furnace and heated to 600-900 ℃ at 2-10 ℃ / min under a nitrogen atmosphere. After holding at this temperature for 1-3 h, it is naturally cooled to room temperature. Then, it is subjected to reduction pretreatment at 300-500 ℃ at 5-15 ℃ / min under a 3-10 vol% H2 / Ar atmosphere. After holding at this temperature for 1-3 h, it is naturally cooled to room temperature to obtain the CuCo-N / CB catalyst.
4. The method for preparing the CuCo-N / CB catalyst according to claim 3, characterized in that, In step (1), the amount of Co carried per gram of CB is 1.0–5.0 mmol·g. -1 CB, with a Cu loading of 0.1–2.0 mmol / g per gram of CB. -1 CB.
5. The method for preparing the CuCo-N / CB catalyst according to claim 3, characterized in that, In step (2), the amount of 1,10-phenanthroline supported per gram of CB is 1.0–8.0 mmol·g. -1 CB.
6. The method for preparing the CuCo-N / CB catalyst according to claim 3, characterized in that, In step (1), the amount of Co carried per gram of CB is 1.5-3.0 mmol·g. -1 CB; each gram of CB carries 0.5-1.0 mmol·g of Cu. -1 CB; in step (2), each gram of CB carries 3.0-4.0 mmol·g of 1,10-phenanthroline. -1 CB.
7. The method for preparing the CuCo-N / CB catalyst according to claim 3, characterized in that, In step (5), the calcination temperature is 800 ℃ and the reduction temperature is 400 ℃.
8. An application of a CuCo-N / CB catalyst, characterized in that, The application of 5-hydroxymethylfurfural in the preparation of 2,5-furandicarboxylic acid is achieved through the following steps: 5-Hydroxymethylfurfural (HMF), CuCo-N / CB catalyst, and potassium hydroxide were added to a reaction vessel. Water was used as the reaction solvent, and oxygen was introduced into the reaction vessel as an oxidant. An intermittent oxidation reaction was carried out under magnetic stirring to produce 2,5-furandicarboxylic acid.
9. The application of the CuCo-N / CB catalyst according to claim 8, characterized in that, The HMF oxidation reaction was carried out at a temperature of 60–100 °C, an oxygen pressure of 1–4 MPa, and a reaction time of 1–9 h.
10. The application of the CuCo-N / CB catalyst according to claim 9, characterized in that, The HMF oxidation reaction was carried out at a temperature of 80 °C, an oxygen pressure of 3 MPa, and a reaction time of 7 h.
